Parlament socjalistyczny: [Socialist parlament] (Studia Prawnicze / The Legal Studies, 1981)
Pointing out features characteristic for socialist Parlaments the Author stresses the fact that they guarantee general representation of the will and interests of all the nation. Depending upon the form of state - unitary or federal - so- cialist Parlaments are either one- or two-chambers organs.As a central organ of state power socialist parlament is the only organ com- petent to regulate the most important state problems and to define the extent of regulation in the form of laws. In socialist countries the parlament occupies the most meaningful position in the system of state organs. It adopts constitution, plan and bud jet of the state, and it is not subjected to the control of any other organ.The principle of unity of state power is fully realized in the activity of the socialist representation. Competences of the parlament include law-making, exe- cutory and controlling activity. These functions are fulfilled by commissions and deputees on their sessions.Presenting the forms of work of socialist Parlaments the Author characterizes the relation between law-making, highest management and controlling activity. Law-making process is ameliorated by making use of scientific principles and by planification. Development of socialist democracy promotes the increase of the role of the parlament, i.e. of the organ which allows all the nation to participate in exercise of state power. The highest state management is realized first of all by way of adopting plans of socio-economic development and the budjet, by ratification of international agreements and by controlling other state organs.In order to strengthen the role of the parlament, mechanisms of its activity are improved and in particular, operating of its comissions. Parlaments of the socialist states differ as far as number of their permanent commissions is concerned; in Bulgaria there are six of them and they cooperate closely with the respective councils of the State Council.The development of cooperation between socialist states requires also streng- thening of ties between their Parlaments, and in particular, integration of their law-making activity.